Experimental and thermodynamic investigations on the chlorine-induced corrosion of HVOF thermal sprayed NiAl coatings and 304 stainless steels at 700 °C - Bai, Mingwen; Reddy, Liam; Hussain, Tanvir (Elsevier, 2018)
Alumina-forming β-NiAl coatings were deposited by high Velocity Oxy-fuel (HVOF) thermal spray onto 304 stainless steels for protection against chlorine induced corrosion in a biomass-fired boiler. The corrosion test was conducted in a synthetic gas containing 500 ppm HCl with 10 wt% KCl ash deposit at 700 °C for 250 hours. Severe corrosion was observed with the fast growing alumina at the coating/substrate interface initiating from sample edges. Possible corrosion mechanism was proposed: as supplied by HCl/KCl, the formation of volatile chlorine/chloride acted as a catalyst and promoted the growth of alumina at relatively lower application temperatures (<900 °C).